The Efficacy of Medical Honey on Achilles Tendon Injury in Dogs (Biochemical Study - Sadaq , Ahmad j.; M, Rafid; Naeem, Naeem (Journal of Neonatal Surgery, 2025)
Objective: The goal of this study is to assess clinically and biochemicaly (Hydroxyproline content) the effect of medical honey on tendon injury. Materials and methods: 18 adult dogs were used for this study. Under general anesthesia and following aseptic technique, core lesions (defects) in the all animals left Achilles tendons were created by multiple perforations of needle gauge 18. All animals were classified into three groups according to local treatment; negative control (normal tendon from the right Achilles tendons), positive control (injured tendon treated with 0.9 % NaCl) and medical honey treated groups. Clinical evaluation and hydroxyproline content of the injured tendons were performed in different times post tendon injury. Results: after 6- and 9-days’ post-surgery, there were significant decreasing lameness scores in the group that received medical honey as opposed to the control group. There was no difference in the operative site swelling between the honey-treated group and the positive control after the third- and sixth-days following surgery. However, the positive control group significantly showed decrease in swelling more than treated group at 12-, 15-, and 18-days post tendon injury. After 45 days' post-surgery, there was notable elevation in hydroxyproline levels in the honey-treated medical group as opposed to the control group., however, the negative control group still significantly have the higher content. Conclusion: Medical honey had analgesic, cost effective and positive impact on tendon tissue regeneration; the healing process periods was minimally reduced due to a maximal amount of hydroxyproline formation, in compare with positive control..